Modelling and optimization of a flexible poly(vinyl chloride) compound formulation for mine cables. (26th January 2018) - Fechter, Reinhard H.; Sandrock, Carl; Kühnert, Ines; Labuschagné, F.J.W.J.
Abstract : Developments by Labuschagné et al. (Patent, WO 2006/123284 A2, 2006) in the manufacture of Layered Double Hydroxides (LDHs) have led to a patent describing a new effluent free synthesis method. A promising application for the LDH is as an additive for a flexible poly(vinyl chloride) (PVC) compound used for the insulation for cables used in South African underground mines. Consequently, a new formulation is required. Unfortunately formulating a PVC compound is a complex problem. The purpose of the investigation is to develop a method that can be used to find an optimum PVC formulation where the material requirements are met while also allowing for the quantitative analysis of the effect of the ingredients on the material properties. This is achieved by modeling the thermal stability, fire retardancy, and basic mechanical properties of the compound as a function of the relative proportions of the ingredients using 2nd order Scheffé polynomials. The empirical models are determined using statistical experimental design. Each model is interpreted using statistical analysis of the model terms which allows for the quantification of the effects and interactions of all the ingredients on the various response variables. The models are also used as constraints in the optimization of the PVC formulation for minimum cost. Parametric analyses are done to demonstrate how the optimization can be used to analyze the entire system taking into account the cost performance of the ingredients. Finally, it is demonstrated how the above approach requires significantly less time and labor to find an optimum formulation than the traditional approach. J. VINYL ADDIT. TECHNOL., 25:E44–E58, 2019. © 2017 Society of Plastics Engineers